OPINION OF STUDENTS REGARDING THE RELEVANCE OF THE VALUES ​​MENTIONED IN RAMACHARITMANAS IN NATIONAL EDUCATION POLICY 2020 - Chaudhary, Omvati (International Journal of Research -GRANTHAALAYAH, 2025)
This research paper was to study the opinion of students regarding the moral values ​​mentioned in Ramacharitmanas and their relevance in National Education Policy 2020 (NEP 2020). Survey method has been used in the present study. 150 boys and 150 girls have been selected for the sample. A self-made tool has been used to collect the data and the collected data has been analyzed by percentage. It is clear from the conclusion that most of the students find the values ​​mentioned in Ramacharitmanas very necessary in modern education and their inclusion in NEP 2020 is relevant.